AB0180 Relationship between area level socio-economic deprivation and autoantibody status in rheumatoid arthritis patients: Multicentre cross-sectional study. (23rd January 2014) - Mackie, S.L.; Taylor, J.C.; Twigg, S.; Martin, S.G.; Steer, S.; Worthington, J.; Barton, A.; Wilson, A.G.; Hocking, L.J.; Young, A.; Emery, P.; Barrett, J.H.; et al.
Abstract : Background: Socio-economic deprivation is known to be associated with an adverse prognosis in rheumatoid arthritis (RA); some of this may be due to differential interaction of individuals with their healthcare providers after symptom onset. Rheumatoid factor (RF) and anti-citrullinated peptide antibody (ACPA) status can precede clinical onset of RA by up to ten years and thus may provide a unique insight into factors affecting immunological events in the pre-clinical stage. In support of this, ACPA-positive and ACPA-negative RA have distinct genetic and environmental risk factors. Objectives: To assess the association between area level socio-economic deprivation and the phenotype of RA, defined by RF and ACPA status, and to determine whether any observed association can be explained by smoking. Methods: Logistic regression analysis of 6298 patients with RA, defined by American College of Rheumatology classification criteria modified for genetic studies. Analysis was stratified by cohort/recruitment centre. Socio-economic deprivation was measured using the Townsend index. Results: Deprivation predicted RF but not ACPA positivity, independent of smoking. The odds ratios (OR) for trend across tertiles of deprivation, adjusted for smoking, gender, period of birth and cohort/recruitment centre, were: 1.14 (95% confidence interval (CI) 1.01 to 1.29) for RF, and 1.01 (95% CI 0.87 to 1.16) for ACPA. Even after adjusting for deprivation, smoking was strongly associated with ACPA positivity (OR 1.38, 95% CI 1.22 to 1.55). There was no evidence of any effect modification by the RA risk alleles ( HLA-DRB1 shared epitope and PTPN22 rs2476601) that are known to modify the effect of smoking on ACPA and RF positivity. Conclusions: Amongst patients with RA, deprivation predicted RF positivity, but not ACPA positivity. The effect of deprivation did not appear to be explained by smoking. We avoided case-control response bias by performing a case-only analysis. Deprivation may be a marker for previously-unrecognised, potentially modifiable environmental influences on the immunological phenotype of RA. Furthermore, given the known associations of RF positivity with prognosis and response to treatment in RA, these findings have potential implications for resource allocation and healthcare delivery. Disclosure of Interest: None Declared